Computational Engineering of Historical Memories With a Showcase on Afro-Eurasia (ca 1100-1500 CE) - Nanetti, Andrea (Taylor & Francis, 2023)
Nanetti outlines a methodology for deploying artificial intelligence and machine learning to enhance historical research. Historical events are the treasure of human experiences, the heritage that societies have used to remain resilient and express their identities. Nanetti has created and developed an interdisciplinary methodology supported by practice-based research that serves as a pathway between historical and computer sciences to design and build computational structures that analyse how societies create narratives about historical events. This consilience pathway aims to make historical memory machine-understandable. It turns history into a computational discipline through an interdisciplinary blend of philological accuracy, historical scholarship, history-based media projects, and computational tools. Nanetti presents the theory behind this methodology from a humanities perspective and discusses its practical application in user interface and experience. An essential read for historians and scholars working in the digital humanities.